School Community Education and Empowerment: Utilizing Microscope Teaching Aids to Cultivate Interest in Learning Science at SMPN Satap 1 Jerowaru : Edukasi dan Pemberdayaan Komunitas Sekolah: Pemanfaatan Alat Peraga Mikroskop untuk Menumbuhkan Minat Belajar Sains di SMPN Satap 1 Jerowaru - Lalu Muhammad Rispan Sugi Saputra; Nurul Hidayah; Wahyuni Arafani (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
Limited access to science laboratory facilities in remote schools often decreases students’ interest in learning science, creating a need for more meaningful learning experiences. This study aimed to enhance student engagement in science learning through the use of microscopes and school community empowerment at SMPN Satap 1 Jerowaru. A participatory approach was employed, consisting of an initial needs assessment, structured training on microscope operation, guided classroom implementation, and evaluation through observations, interviews, and student questionnaires. Data were analyzed descriptively to assess changes in students’ motivation and participation, as well as improvements in teachers’ competencies. The results show a significant increase in students’ motivation, curiosity, and active participation, reflected in questionnaire scores categorized as “Very Good” and “Good.” Teachers also demonstrated enhanced skills in integrating microscope-based activities into science lessons. The study concludes that microscope-based learning supported by an empowered school community can serve as an effective and sustainable model for schools with limited laboratory facilities. Scientifically and practically, these findings highlight the need for broader implementation and further development of community-supported laboratory practices to strengthen scientific literacy in similar contexts.